PENGARUH KONFIGURASI RUANG TERHADAP KENYAMANAN TERMAL PENGGUNA GEDUNG DI DAERAH BERIKLIM TROPIS LEMBAP - Utomo, Pandu K.; Sari, Dharwati P.; Nanda, Harta D.; Nurjannah, Cindy U. (Jurnal Arsitektur ZONASI, 2023)
Laboratory Building FT Unmul is a building located in humid tropical climate. With humans carrying out various activities, thermal comfort needs to be measured to find out how the building represents a good tropical building. This research was carried out using the Predicted Mean Vote (PMV) model which collaborates on personal variables and spatial variables. Measurements were carried out in several rooms inside the Laboratory Building, using thermal comfort software. The results of this study indicate that without air-conditioning, rooms that are directly exposed to sunlight do not provide thermal comfort while other rooms are able to achieve that. Meanwhile, with artificial ventilation intervention, most of the space does not increase the thermal comfort for the user. These results can be taken into consideration in the design (space configuration) and building management (room management and building energy consumption).